Spread of CTX-M-15 positive Providencia spp. causing urinary tract infections at the University Hospital Split in Croatia - Barl, Petra; Bedenić, Branka; Sardelić, Sanda; Uzunović, Selma; Vraneš, Jasmina; Plečko, Vanda (Medicinski glasnik, 2012)
During 2010-2011, six Providencia spp. (five Providencia stuartii and one Providencia rettgeri) urine isolates with unusual resistance phenotype were collected from various hospital units at the University Hospital Split in Croatia. The aim of the study was to analyze the mechanisms of resistance to expanded-spectrum cephalosporins. The antimicrobial susceptibility to a wide range of antibiotics was determined by broth microdilution method according to CLSI guidelines. A double-disk-synergy test (DDST) was performed to detect ESBLs. The transferability of cefotaxime resistance was determined by conjugation. The presence of genes encoding ESBLs was determined by PCR while genotyping of the isolates was performed by PFGE. All strains were positive for ESBL production by DDST. They were uniformly resistant to amoxycillin alone and combined with clavulanate, cefazoline, cefuroxime, ceftazidime, cefotaxime, ceftriaxone, gentamicin and ciprofloxacin. P. stuartii strains transferred cefotaxime resistance to E. coli recipient strain with frequency ranging from 10-5 to 5x10-4. Five P. stuartii strains were positive for TEM and CTX-M β-lactamases while P. rettgeri was positive only for TEM β-lactamases. Five CTX-M producing isolates were shown to be clonally related. Continuous surveillance in tracking CTX-M-15- producing P. stuartii in the hospitals is necessary to prevent their spread to other hospitals and community. Global spread of ESBL positive Providencia spp all over the world is of great clinical concern.